Examining the factors influencing teleconsultation adoption during the pandemic using the TAM model - San Ekaimi; Prio Utomo; Djohan Gunawan; So Yohanes Jimmy; Michael Christian (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this study is to understand patients' behavior in adopting teleconsultation services during the pandemic which has accelerated technology adoption in various sectors and regions in unnatural ways through experimentation in the wide-spread adoption of telemedicine specifically in teleconsultation. Design/methodology/approach: The study is cross-sectional quantitative research with purposive sampling that was analyzed using the partial least squares structural equation model (PLS-SEM) with data gathered from 100 patients who used tele-consultation services during the pandemic. The technology adoption model (TAM) was used to frame the phenomenon as previous study revealed that TAM is most suitable to understand technology adoption in the healthcare industry. Findings: The analysis revealed that trust, ease of use, and privacy are significant latent variables that influence the intention and actual use of the tele-consultation services, while the usefulness of the services insignificantly influences the intention to use. The study revealed that trust is the dominant factor despite the emergency and experimentation state of patients to get healthcare services during the pandemic. Self-preservation, and the patients accumulated experience they had with the healthcare services provider are the determinants of this behavior based on theory and confirmative interview. Research limitations/implications: The implication of this research opens interdisciplinary future research and practical action on the relationship between healthcare provider, patient experience, self-preservation, and technology adoption during the emergency and pandemic era. Research Limitation: Early system usage and adopter focused, limited system quality and reliability, and generalization are the limitation of this research. Originality/value: The study provides insight into factors that influence the adoption and usage of tele-consultation experimentation health services during a pandemic.
Keywords: 650; telemedicine; teleconsultation; healthcare; PLS-SEM; TAM; pandemic